Effects of Core Disgust and Moral Disgust on Moral Judgment: An Event-Related Potential Study - Tao, Dan; Leng, Yue; Huo, Jiamin; Peng, Suhao; Xu, Jing; Deng, Huihua (Frontiers in Psychology, 2022)
Core disgust is elicited by physical or chemical stimuli, while moral disgust is evoked by abstract violations of moral norms. Although previous studies have pointed out these two types of disgust can affect behavior and spatial dimensions of moral judgment, less is known about how moral and core disgust affect the temporal neural processing of moral judgment. In addition, whether moral and core disgust are only related to purity-based moral judgment or all kinds of moral judgment is still controversial. This study aimed to explore how core and moral disgust affect the neural processing of purity-based moral judgment by using affective priming and moral judgment tasks. The behavioral results showed that the severity of moral violation of non-purity ones is higher than purity ones. The ERP results mainly revealed that earlier P2 and N2 components, which represent the automatic moral processes, can differentiate neutral and two types of disgust rather than differentiating moral domain, while the later N450, frontal and parietal LPP components, which represent the conflict detection and later cognitive processing can differentiate the purity and non-purity ones rather than differentiating priming type. Moreover, core and moral disgust priming mainly differed in the purity-based moral processing indexed by parietal LPP. Our findings confirmed that the disgust effect on moral judgments can be explained within the framework of dual-process and social intuitionist models, suggesting that emotions including core and moral disgust played an essential role in the automatic intuition process. The later parietal LPP results strongly supported that core disgust only affected the purity-based moral judgment, fitting the primarily purity hypothesis well. We show how these theories can provide novel insights into the temporal mechanisms of moral judgment.